Adaptive Dynamic Programming for Robust Regulation and Its Application to Power Systems - Yang, Xiong; He, Haibo; Zhong, Xiangnan (IEEE transactions on industrial electronics (1982), 2018)
This paper presents a novel robust regulation method for a class of continuous-time nonlinear systems subject to unmatched perturbations. To begin with, the robust regulation problem is transformed into an optimal regulation problem by constructing a value function for the auxiliary system. Then, a simultaneous policy iteration (SPI) algorithm is developed to solve the optimal regulation problem within the framework of adaptive dynamic programming. To implement the SPI algorithm, actor and critic networks are employed to approximate the optimal control and the optimal value function, respectively, and the Monte Carlo integration method is applied to obtain the unknown weight parameters. Finally, two examples, including a power system, are provided to demonstrate the applicability of the developed approach.